Moderate Ischemic Mitral Insufficiency at the Time of Coronary Artery Bypass Graft; Repair or Spare? - Abdelwahhab, Ahmed; Rushdi, Mohamad; Ayyad, Mohamed; Elminshawy, Ahmed (AL-Kindy College Medical Journal, 2024)
Background: Approximately 13-59% of myocardial infarction patients develop ischemic mitral regurgitation, impacting left ventricular function and increasing mortality risk. Optimal management of moderate ischemic mitral regurgitation remains controversial, raising the question of whether adding mitral valve surgery to coronary artery bypass graft (CABG) has an overall advantage over revascularization or not. Objective: To investigate the early and mid-term comparison between the two techniques. Subjects and Methods: This randomized clinical trial was conducted at Assuit University Heart Hospital, on 50 patients randomized into two groups: Group A: 25 patients underwent CABG and Group B: 25 patients had CABG and mitral valve repair. Inclusion criteria was multi-vessel coronary artery disease, moderate ischemic mitral regurge (MR). All patients were subjected to full history taking, routine physical, laboratory investigations and transthoracic echocardiography. Intraoperative data was collected. Early outcomes included MR degree, and left ventricular (LV) diameters and function, ICU stay duration, and in-hospital mortality. Mid-term outcomes included MR degree, LV diameter and function. Results: Groups had similar age and gender distribution. Repair procedures showed longer ischemic and operative times than CABG alone (P≤0.0001 and P=0.0012). Early post-operative, repair reduced MR significantly (P≤0.0001). At six months follow-up, CABG group had more rate of improvement than repair group (P≤0.0001). Conclusions: In moderate ischemic mitral regurgitation with multi-vessel ischemic heart disease, adding mitral valve repair to CABG may reduce mitral regurgitation severity early and at six months compared to CABG alone. However, CABG alone offers shorter ischemic times and operative durations.